A cultural studies approach to semantic instability: The case of news translation - Conway, Kyle (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article explores news translation and the semantic instability of politi-cally charged words and their translations. Such pairs are linked in a pa-radoxical relationship of dependence (one is a translation of the other) and independence (they have evolved and continue to evolve within different conceptual horizons). This paper describes a methodology for addressing this phenomenon by considering such pairs as examples of ‘essentially contested concepts’ (Gallie 1956). This methodology derives from a circuit model of culture, and it provides translation studies scholars with tools to describe the dynamic, historically conditioned relationships linking politi-cally charged words, their translations, and their contested, frequently contradictory meanings.